The Crossroads of Periodontitis and Oral Squamous Cell Carcinoma: Immune Implications and Tumor Promoting Capacities - Elebyary, Omnia; Barbour, Abdelahhad; Fine, Noah; Tenenbaum, Howard C.; Glogauer, Michael (Frontiers in Oral Health, 2021)
Periodontitis is increasingly considered to interact with and promote a number of inflammatory diseases, including cancer. In the case of oral squamous cell carcinoma (OSCC) the local inflammatory response associated with PD is capable of triggering altered cellular events that can promote cancer cell invasion and proliferation. Both the immune and stromal components of the periodontium exhibit phenotypic alterations and functional differences during PD that result in a microenvironment that favours cancer progression. The inflammatory milieu in PD is ideal for cancer cell seeding, migration, proliferation and immune escape. Understanding the interactions governing this attenuated anti-tumour immune response is vital to unveil unexplored preventive or therapeutic possibilities. Here we review the many commonalities between the oral-inflammatory microenvironment in PD and oral-inflammatory responses that are associated with OSCC progression, and how these conditions can act to promote and sustain the hallmarks of cancer.